(untitled) (Raparin Journal of Humanities (RJH), 2022)
All the respected companions and especially their scholars lived during the period of the revelation of the Qur’an to the Prophet, And they were aware of all the events which the Qur’an was revealed for ,also they were aware of the time and situation of the revelation. God has been gracious and merciful to them and he had prepared them to receive this holy revelation. And they also cared about the goals of the shariat in general and They considered the reasons of this revelation, they were trying to deduce the law specific to the Qur’an and the shariat. According to the shariat they determined the solution of new events, they linked reality to the Qur’an, Because the holy message of Islam is a message that has several general and appropriate laws for all advanced and non-advanced communities, the message of God is the only message that can lead humanity to happiness And give them peace. Each of these companions had a pure heart, and the light of the message of God and the Prophet was in them. One of these esteemed companions was Abdullah Ibn Mas’ud, who was a great companion and the owner of the school) belief and understanding), he had his own reasons for deriving the laws of th Qur’an and Sunnah. He had his own reasons for inferring the laws of the Qur’an and Sunnah, including the Holy (Qur’an, the Prophetic Sunnah, accepting, inferring(.